2016
DOI: 10.21037/tgh.2016.03.23
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid surgery for early gastric cancer

Abstract: Endoscopic submucosal dissection (ESD) is the most suitable treatment option in terms of minimally invasive treatment for potential node-negative early gastric cancers (EGCs). Furthermore, making the resection area of the primary lesion as small as possible is ideal for the patient's quality of life, even for potential node-positive EGC. An endoluminal approach is a reasonable option with which to minimize stomach resection area, because this procedure can be accurately demarcated from the inside. From this po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 31 publications
(30 reference statements)
0
9
0
Order By: Relevance
“…Goto et al reported NEWS for early gastric cancer in combination with sentinel node (SN) navigation surgery. The SN is defined as the first lymph node that receives lymphatic drainage from the primary tumor site.…”
Section: Future Potential For Laparoscopic Endoscopic Cooperative Surmentioning
confidence: 99%
“…Goto et al reported NEWS for early gastric cancer in combination with sentinel node (SN) navigation surgery. The SN is defined as the first lymph node that receives lymphatic drainage from the primary tumor site.…”
Section: Future Potential For Laparoscopic Endoscopic Cooperative Surmentioning
confidence: 99%
“…Endoscopic full-thickness resection (EFTR) is usually done with laparoscopic assistance to facilitate safe resection of the lesion, repair of the ensuing defect, and even limited lymph node dissection. 49 Dissection is done intraluminally with submucosal injection and circumferential endoscopic mucosal incision, followed by intentional perforation to facilitate complete full thickness resection under laparoscopic countertraction. 50 Iatrogenic tumor seeding is a concern with this procedure since there is a possibility of tumor cells in the gastric juice to spread by spillage or by contact of exposed surface of the lesion with the peritoneum or laparoscopic instruments.…”
Section: Endoscopic Resectionmentioning
confidence: 99%
“…50 Iatrogenic tumor seeding is a concern with this procedure since there is a possibility of tumor cells in the gastric juice to spread by spillage or by contact of exposed surface of the lesion with the peritoneum or laparoscopic instruments. 49 Non-exposure techniques for full-thickness resection have been developed to prevent iatrogenic seeding such as wedge resection, combination of laparoscopic and endoscopic approaches to neoplasia with non-exposure technique (CLEAN-NET), and non-exposed endoscopic wall-inversion surgery (NEWS). 49…”
Section: Endoscopic Resectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Goto et al reported NEWS for early gastric cancer in combination with sentinel node (SN) navigation surgery (12,18). The SN is the first lymph node that receives lymphatic drainage from the primary tumor.…”
Section: Future Perspectives For Lecs Proceduresmentioning
confidence: 99%